Pelatihan Pengembangan Organisasi Kepemudaan Satuan Pemuda-Pemudi Dirgantara Asri (SAPDA) - Ali Mahmud Ashshiddiqi (UII, 2019)
Satuan Pemuda-Pemudi Dirgantara Asri (SAPDA) is a growing youth organization in Perumahan Dirgantara Asri, Jragung, Jogotirto, Berbah, Sleman, Yogyakarta. On the one hand, this organization has a significant contribution and, on the other hand, has organizational effectiveness problems. This community service activity was carried out to provide a solution to the problem and strengthen the existence of the SAPDA organization as a social element that accommodates the actualization of the role of youth and as an essential subject of the regeneration process in Perumahan Dirgantara Asri.Community service here takes the format of organizational development training which consists of three sustainable activities, namely: focus group discussion (FGD), outbound, and training. These activities target every individual member of SAPDA as well as all SAPDA members as a group. Training is oriented towards increasing motivation to organize through FGD activities, and strengthening the capacity of team building through outbound activities. As a reinforcement of the results of the FGD and outbound activities, the activity continued with organizational development training. Overall, three service activities are arranged systematically to be relevant and effective in addressing the problems faced by SAPDA as partner institutions.Three service activities fulfill the principle of sustainability and are oriented towards increasing the effectiveness of the SAPDA organization. The FGD encouraged the emergence of self-awareness about the importance of organizational motivation and participant sensitivity to the condition of the organization. Outbound has an influence on shared awareness about the importance of team building strengths in the organization. While the training provides psychological reinforcement and highlights the main values contained in the previous two activities. Based on the results of this activity, the service provider gave suggestions to SAPDA itself and other service activities oriented to the development of youth organizations.